Avaliação dos parâmetros espermatogênicos de ratos Wistar portadores de diabetes mellitus tipo 2 induzida por meio de dieta hipercalórica - Bárbara Ramalho Ladeira Cardoso (2021)
Diabetes mellitus is a chronic disease related to metabolic disorders such as hyperglycemia due to peripheral resistance and/or low insulin production. Type 1 DM is an autoimmune disease characterized by a loss of function of pancreatic β-cells to secrete insulin. Type 2 DM is correlated with a sedentary lifestyle, high-calorie diets, obesity and stress. Type 2 DM has been diagnosed earlier in the population and, according to the WHO, in 2014 there were about 442 million people with diabetes in the world. So, knowing that diabetes has systemic consequences, there is a concern about male fertility, since it has been observed that diabetic men have altered seminal parameters and reduced testosterone levels leading to infertility. Previous studies describe spermatogenesis and morphofunctional changes in sperm. However, in large part, the data found are from drug induction through streptozotocin. However, since the clinical course of diabetes is associated with behavioral factors such as hypercaloric eating, our project investigated the effects of type 2 DM using a diet protocol that is able to mimic the pathophysiology of the disease. Thus, Wistar rats were treated with a high-calorie diet for a period of 30 and 90 days. The effects of the high-calorie diet on blood glucose and biometric parameters in 30-day-old animals did not show significant difference, although in 90-day-old animals blood glucose and body weight were significantly increased, resulting in a reduction in the IGS in this group. Although there are no marked changes in the organization of the testicular parenchyma, Leydig cells responded in a dichotomous way to the 30- and 90-day interventions. Compensatory hyperplasia, characterized by cells with smaller individual volume, represented the response of Leydig cells to intervention for 30 days. On the other hand, prolonged intervention with a hypercaloric diet generated a steroidogenic cell response typical of hypertrophy, where the cells increased their individual volume, mainly in the cytoplasmic compartment. Despite the reduced number of cells, volumetric adaptations marked the attempt to maintain homeostasis in the synthesis of sex steroids. Furthermore, the expression of the 3beta-HSD enzyme, which was lower in the 30-day group (p < 0.05), was already similar to the control in the 90-day group.